Effect of Extracts of Cryopreserved Piglet Skin Fragments on State of Pro- and Antioxidant Systems Following Skin Cryodestruction - Vlasov, Aleksandr A.; Kovalov, Gennadiy A.; Belochkina, Irina V.; Tynynyka, Lyudmila N.; Sandomirsky, Boris P. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):170.